Winnipeg gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series - Compton, Jim; Deerchild, Rosanna; Farmer, Gary; Kulchyski, Peter; Monkman, Lenard; Morrisseau, Miles; Ouellette, Robert-Falcon; Philips, Trevor; Spillet, Leslie; Wheeler, Kim; Buddle, Kathleen; Gagnon, John (Université d'Ottawa | University of Ottawa, 2017)
A collection of documents, audio recordings, and programming resulting from the first gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series held in Winnipeg, Manitoba on February 17th, 2017.
Keywords: First Nations; Inuit; Métis; Radio; Broadcasting; Magazine; Policy; Canada